Kinetic Model for the ATP-Dependent Translocation of Saccharomyces cerevisiae RSC along Double-Stranded DNA - Fischer, Christopher J. (2007)
The chromatin remodeling complex RSC from Saccharomyces cerevisiae is a DNA translocase that moves with directionality along double-stranded DNA in a reaction that is coupled to ATP hydrolysis. To better understand how this basic molecular motor functions, a novel method of analysis has been developed to study the kinetics of RSC translocation along double-stranded DNA. The data provided are consistent with RSC translocation occurring through a series of repeating uniform steps with an overall processivity of P = 0.949 ± 0.003; this processivity corresponds to an average translocation distance of 20 ± 1 base pairs (bp) before dissociation. Interestingly, a slow initiation process, following DNA binding, is required to make RSC competent for DNA translocation. These results are further discussed in the context of previously published studies of RSC and other DNA translocases.